Navigating the intellectual property landscape of Formula 1: trademarks and branding strategies - Jaunozola, Ketlīna Krista (Riga Graduate School of Law, 2024)
This thesis explores the interlink between law and business in the field of motorsport – Formula 1 – going into the area of intellectual property (IP), its opportunities and challenges. Analysing trademark protection, registration, branding strategies and monetization brings a bigger understanding of how teams, sponsors and stakeholders deal with legal problems and how they can find the perfect balance between the sport and policymaking. By addressing the research question and conducting a comprehensive analysis using European legislation, this thesis provides a clear insight into how complex the dynamics of intellectual property are behind the scenes of Formula 1. Incorporating official documents and real-life case studies, this study demonstrates that Formula 1 is the most advanced motorsport in the world and intellectual property plays a pivotal role in successfully branding it to the world.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Private law::Intellectual property law; Trademarks; Formula 1